Impacts of hypoxic events surpass those of future ocean warming and acidification - Sampaio, Eduardo (2021)
Over the past decades, three major challenges to marine life have emerged as a consequence of anthropogenic emissions: ocean warming, acidification and oxygen loss. While most experimental research has targeted the first two stressors, the last remains comparatively neglected. Here, we implemented sequential hierarchical mixed-model meta-analyses (721 control–treatment comparisons) to compare the impacts of oxygen conditions associated with the current and continuously intensifying hypoxic events (1–3.5 O2 mg l−1 ) with those experimentally yielded by ocean warming (+4 °C) and acidification (−0.4 units) conditions on the basis of IPCC projections (RCP 8.5) for 2100. In contrast to warming and acidification, hypoxic events elicited consistent negative effects relative to control biological performance—survival (–33%), abundance (–65%), development (–51%), metabolism (–33%), growth (–24%) and reproduction (–39%)—across the taxonomic groups (mollusks, crustaceans and fish), ontogenetic stages and climate regions studied. Our findings call for a refocus of global change experimental studies, integrating oxygen concentration drivers as a key factor of ocean change. Given potential combined effects, multistressor designs including gradual and extreme changes are further warranted to fully disclose the future impacts of ocean oxygen loss, warming and acidification.